Role of motor simulation in anticipation of free throws in basketball - Unenaka, S.; Nakamoto, H.; Ikudome, S.; Mori, S. (Japanese Journal of Sport Psychology, 2014)
The present study aimed to clarify the contribution of motor simulation during action observation to anticipation skill in sports. Therefore, the influence of concurrent motor execution during observation on the accuracy of anticipating basketball free throws was examined. Eighteen right-handed male basketball players (skilled) and 18 right-handed males with no basketball experience (non-skilled) anticipated a basketball free throw under the following conditions: control in which participants simply observed free throw actions and right-volar, right-dorsal, left-volar and left-dorsal flexion that required concurrent motor execution during each condition. Anticipation was more accurate in experts than in non-experts under control conditions. Moreover, anticipation accuracy was reduced in experts under right-dorsal flexion compared with the other conditions. In contrast, anticipation accuracy improved in non-experts under right-volar flexion compared with other conditions. These results indicated that concurrent motor execution influences the ability to anticipate action and this effect depends on experience of free throw. These findings suggested that motor simulation is associated with action anticipation in sports expertise